2016
DOI: 10.1209/0295-5075/115/20009
|View full text |Cite
|
Sign up to set email alerts
|

Frequency stabilization by synchronization of Duffing oscillators

Abstract: We present analytical and numerical results on the joint dynamics of two coupled Duffing oscillators with nonlinearity of opposite signs (hardening and softening). In particular, we focus on the existence and stability of synchronized oscillations where the frequency is independent of the amplitude. In this regime, the amplitude-frequency interdependence (a-f effect) -a noxious consequence of nonlinearity, which jeopardizes the use of micromechanical oscillators in the design of time-keeping devices-is suppres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Investigations on synchronization trace back to Huygens' work in 1677 [12]. Presently, synchronization exhibits remarkable performance in sensing, attributed to exceptional frequency stability [13][14][15][16] and the ease of frequency recognition [17]. This has found significant application in microelectromechanical systems (MEMS) owing to their compact size and compatibility with integrated circuit fabrication [18][19][20][21].…”
Section: Introductionmentioning
confidence: 95%
“…Investigations on synchronization trace back to Huygens' work in 1677 [12]. Presently, synchronization exhibits remarkable performance in sensing, attributed to exceptional frequency stability [13][14][15][16] and the ease of frequency recognition [17]. This has found significant application in microelectromechanical systems (MEMS) owing to their compact size and compatibility with integrated circuit fabrication [18][19][20][21].…”
Section: Introductionmentioning
confidence: 95%
“…Substituting Equation (26) into Equation (24) yields the following: Figure 13 shows the variation of the detection error under different quality factors. It was found that the damping is crucial to the accuracy of mass detection.…”
Section: Parameter Identification Based On Frequency Stabilization Anmentioning
confidence: 99%
“…Experimental results showed that the interdependence between the resonance frequency and the vibration amplitude can be limited by the mode interaction in nonlinear micromechanical resonators [ 25 ]. Zanette [ 26 ] studied the joint dynamics of coupled Duffing oscillators with a nonlinearity of opposite signs. Results showed that the frequency stabilization of nonlinear coupled systems can be achieved under appropriate parameter conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This simple model has been used to model memory and logic devices [15,16], neural networks [17,18], the recurrence of Earth's ice ages [20], piezoelectric buckled beams [21] and many other systems. Different aspects of the system were investigated, including the effect of noise on the hysteresis of a single oscillator [22], the noise-induced intermittency of two coupled oscillators [23], chaos and routes to chaos [24,25], synchronization [26,27] and others. Here, using numerical continuation, we found the bifurcation diagram and identified a bistability region of oscillations with the driving period and with the doubled period.…”
mentioning
confidence: 99%